THE EFFECT OF COMPETENCE AND MOTIVATION ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEES CAPABILITIESON PT. BINASINAR AMITY. - DonatusAdiKurniawan, Guswandi & AkhmadSodikin (International Journal of Research Science and Management, 2018)
The purpose of this study is to analyze the influence of competence and motivation on employee performance simultaneously, to analyze the influence of competence and motivation on the ability of employees simultaneously, to analyze the influence of ability to partial employee performance, to analyze the influence of indirect competence. For employee performance through employee ability, indirect motivation on employee performance through employee ability. The object of research is employees at PT BinaSinar Amity. Sampling technique used in this research is probability sampling and simple random sampling. The number of samples in this study was as many as 40 employees of the company. The results show that competence and motivation have a positive effect on employee performance. The direct impact of competence on employee performance is 0.398, while the influence of indirect competence on employee performance through the ability that is equal to 0.491. From the above explanation that the value of direct influence is less than the value of indirect influence that gives the meaning that the ability variable capable of mediating the competence to employee performance. Influence indirectly on employee performance through the proven ability and acceptable. The direct influence of motivation on employee performance that is equal to 0,378, while the magnitude of indirect influence of motivation on the performance of employees through the ability of 0.471. N value of direct influence is less than the value of indirect influence that gives the meaning that the ability of the variable is able to mediate employee performance motivation.